2015
DOI: 10.1139/cjb-2014-0136
|View full text |Cite
|
Sign up to set email alerts
|

Gynoecial ontogeny of Anthurium: contributions for floral developmental studies in Araceae (Alismatales)

Abstract: Studies on floral development have widened the knowledge on the floral morphology of Araceae, particularly in genera delimited through classical taxonomic treatments. In Pothoideae, floral ontogenetic studies are limited to some representatives of Pothoidium Schott and Pothos L. and only one species of Anthurium Schott, with no focus on gynoecium. This background reveals a lack of ontogenetic data on the largest genus in the clade. This paper presents gynoecial ontogeny of species circumscribed in different se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…augustinum K. Koch & Lauche (Cardozo et al, 2014), Barabé, Forget & Chrétien (1984) reported only ventral complexes and placental traces, which diverge from four complexes at the floral base. Thus, an infrageneric variation has been observed in relation to the carpellary vasculature as well as previously indicated for other floral characteristics (Carvajal, 1977; Higaki, Rasmussen & Carpenter, 1984; Carvell, 1989; Poli, Temponi & Coan, 2012; Poli, Temponi & Coan, 2015). These characteristics are contributing to new data toward the understanding of the floral morphology of the genus and may help in the still widely debated infrageneric classification.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…augustinum K. Koch & Lauche (Cardozo et al, 2014), Barabé, Forget & Chrétien (1984) reported only ventral complexes and placental traces, which diverge from four complexes at the floral base. Thus, an infrageneric variation has been observed in relation to the carpellary vasculature as well as previously indicated for other floral characteristics (Carvajal, 1977; Higaki, Rasmussen & Carpenter, 1984; Carvell, 1989; Poli, Temponi & Coan, 2012; Poli, Temponi & Coan, 2015). These characteristics are contributing to new data toward the understanding of the floral morphology of the genus and may help in the still widely debated infrageneric classification.…”
Section: Introductionsupporting
confidence: 80%
“…The apical septum was reported for A . scandens by Poli, Temponi & Coan (2015) as being related to the ovary’s reduced size to accommodate the ovules.…”
Section: Discussionmentioning
confidence: 99%